2015
DOI: 10.17795/ijcp-3428
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Vascular Endothelial Growth Factor (VEGF) and Epidermal Growth Factor Receptor (EGFR) in Patients With Serous Ovarian Carcinoma and Their Clinical Significance

Abstract: Background:Vascular endothelial growth factor (VEGF) has an essential role in tumor metastasis by inducing the construction of abnormal blood vessels. Epidermal growth factor receptor (EGFR) is involved in different parts of cancer growth such as tumor initiation, angiogenesis and metastasis.Objectives:The aim of this study was to evaluate the expression of VEGF and EGFR in ovarian cancer in southern Iran and to assess the correlation between expression of these two markers and patients’ age, tumor stage, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…varian cancer is the sixth most frequent diagnosed cancer among women worldwide, the second most common gynecologic malignancy in females, and the most fatal tumor of female reproductive system [1] . Several genetic and environmental factors have been shown to be implicated in the development of this type of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…varian cancer is the sixth most frequent diagnosed cancer among women worldwide, the second most common gynecologic malignancy in females, and the most fatal tumor of female reproductive system [1] . Several genetic and environmental factors have been shown to be implicated in the development of this type of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Identification of a proper antigen for targeted therapy is a key concept (40). The extracellular part or CRD domain of FZD receptors, which act as binding sites for Wnt ligands, can be targeted by peptides to inhibit binding of wnt ligands thus preventing Wnt/β-catenin signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The extracellular part or CRD domain of FZD receptors, which act as binding sites for Wnt ligands, can be targeted by peptides to inhibit binding of wnt ligands thus preventing Wnt/β-catenin signaling. It has been shown that targeting of special parts of some extracellular domains of cancer cell receptors leads to anti-proliferative effects (36,(40)(41)(42). The specificity of tumor binding and anti-proliferative properties of the selected scFvs suggests that these human high affinity and small anti-FZD7 scFvs might have a therapeutic potential for colorectal cancer targeting therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Ovarian cancer as the most fatal gynecological malignancy has been a subject of screening programs for decades (1,2). Yet no effective screening strategy has been identified so far.…”
Section: Contextmentioning
confidence: 99%